Do Financial Difficulties Hinder the Export of Processing Industries in Transition Countries? – The Case of Mongolia - Neszmélyi , György Iván; Altnaa, Ulziimaa (Studia Mundi – Economica, 2024)
The purpose of this study is to investigate what barriers exporters of the processing industry face during export. The research is a qualitative study that looks at if the country’s origin and the economic and political situation affect exports. Easing poverty and supporting the economy, export has been considered a vital aspect of development for many countries. The number of livestock is one of the crucial factors for the processing industry, but unlike other countries that receive high revenue and benefit from the export of the processing industry, particularly the leather industry, the export share is small in Mongolia. Although many researchers, and policymakers have tried to explore what brings low-value addition and low export share of end products in transition countries, there are only a few articles conducted in the field of the processing industry. The number of livestock and geographical location between China and Russia seem Mongolia has significant potential to thrive leather sector, more scientifically proven research should be conducted to provide insight into what barriers impede the export possibilities for the Mongolian leather industry and try to shed light on the possibilities in a broad range. The authors adopted qualitative research methods and used both primary and secondary data. At the end of the study, we created three main themes from participants’ responses and the result of the study showed there are three distinctive barriers that the leather industry exporters face during export activity.